2020
DOI: 10.1155/2020/3695209
|View full text |Cite
|
Sign up to set email alerts
|

Global Estimates of the Prevalence of Depression among Prisoners: A Systematic Review and Meta-analysis

Abstract: Background. Prison populations tend to be marginalized and disadvantaged of the rights and freedoms that other people in the community benefit from. Their separation from families, a narrow room and lack of privacy in the prison, violence between prisoners, and the uncertainty about the future result in psychological distress, for example, depression. The review has synthesized previous studies conducted on the topic and summarized to formulate recommendations for future prison health care services. Methods. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
18
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 43 publications
4
18
1
Order By: Relevance
“…Beyond the pandemic, situations and contexts which thwart such basic needs can result in psychological distress, and this includes patients having to undergo long-term bedrest, grieving individuals, people with mobility issues, or even incarcerated prisoners, among others ( Maloni et al, 2002 ; Bedaso et al, 2020 ). Video games may provide psychological relief for individuals going through difficult emotional experiences in life.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond the pandemic, situations and contexts which thwart such basic needs can result in psychological distress, and this includes patients having to undergo long-term bedrest, grieving individuals, people with mobility issues, or even incarcerated prisoners, among others ( Maloni et al, 2002 ; Bedaso et al, 2020 ). Video games may provide psychological relief for individuals going through difficult emotional experiences in life.…”
Section: Discussionmentioning
confidence: 99%
“…Given the possibility of under-reporting as well as over reporting of some symptoms such as suicidality, a caseness threshold of 10 or more may be satisfactory for the GAD-7 but not for the PHQ-9. The diagnostic algorithm suggested that only 17.9% prisoners had a depressive episode which is in the expected range for caseness for a depressive episode (15.0-23.9%) when standardised psychiatric interviews were used in previous studies [14]. However, the diagnostic algorithm method tends to have low sensitivity [28] for depressive episodes so it may miss some cases, including some who may be at risk of suicide and selfharm.…”
Section: Discussionmentioning
confidence: 99%
“…Given previous concerns about false positives when screening prisoners for mental health problems with community derived thresholds [14][15][16], we conducted a dendrogram of scores of 3 or more on the core items of the PHQ-9 and GAD-7 in all those who scored > 10 on the PHQ-9. We found five clusters, the largest of which (cluster 3) had daily core symptoms of depression with suicide ideation, poor concentration, feeling slowed down or restless, irritability or fear of something bad happening.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations